Association between preoperative proximal thoracic curve flexibility and postoperative spontaneous correction in Lenke type 1 adolescent idiopathic scoliosis: a retrospective study - Keitaro Minato; Masayuki Ohashi; Kei Watanabe; Toru Hirano; Kazuhiro Hasegawa; Masayuki Sato; Tatsuo Makino; Hideki Tashi; Hiroyuki Kawashima (Scientific Reports)
Abstract Lenke type 1 adolescent idiopathic scoliosis (AIS) is characterized by a structural main thoracic (MT) curve and a non-structural proximal thoracic (PT) curve. Accurate prediction of postoperative PT curve correction is crucial for achieving optimal surgical outcomes, including postoperative shoulder balance. This study aimed to determine which preoperative lateral bending and traction radiographs are most appropriate for assessing spontaneous postoperative PT curve correction. Fifty-five patients with Lenke type 1 AIS who underwent PSF between January 2006 and January 2020 were included. Preoperative curve flexibility was assessed using side-bending (SB), fulcrum-bending (FB), and traction (TR) radiographs. Radiographic measurements were conducted preoperatively, immediately postoperatively, and at the 2-year follow-up. The average preoperative Cobb angles for PT, main thoracic (MT), and thoracolumbar/lumbar (TL/L) curves were 24.7°, 53.5°, and 32.4°, respectively. SB radiographs demonstrated a significant correlation with 2-year postoperative PT Cobb angles (r = 0.526, p < 0.001), with no significant difference between preoperative SB measurements and actual 2-year postoperative outcomes (mean difference − 0.03°; 95%CI − 1.57 to 1.49; p = 0.88). FB radiographs accurately reflected MT correction but overestimated PT correction (mean difference 2.29°; 95%CI − 0.51 to 5.10; p = 0.11), while TR radiographs underestimated PT correction. These results indicate that SB radiographs can be used as a reliable reference for estimating postoperative spontaneous PT curve correction in Lenke type 1 AIS.